Enhancement of Solubility and Dissolution Rate of Lumefantrine by Pharmaceutical Cocrystals (Asian Journal of Pharmaceutics (AJP), 2023)
The solid-state properties of drug compounds, such as solubility and dissolution, can be changed bycocrystallizing the drug with coformers. The purpose of the current effort was to identify potential coformers andthen develop, formulate, and assess the lumefantrine cocrystal. Methods: Lumefantrine cocrystals were createdusing the solvent evaporation process. The crystalline phase’s melting temperature and solubility were established.DSC, IR, and XRPD were used to characterize the putative cocrystal. Evaluations were also conducted onsolubility and dissolution rate, two additional medicinal qualities. Results and Discussion: Lumefantrine-adipicacid cocrystals showed a range in solubility and melting points. Adipic acid and the cocrystals were combinedin a 1:1 ratio. The infrared research clearly showed that the lumefantrine distinctive bands were changing.A notable variation in the 2θ of the strong peaks and the crystallinity of cocrystals were indicated by the X-raypowder diffraction pattern. Cocrystal’s differential scanning calorimetry spectra revealed changed melting pointendotherms. Due to cocrystallization, the cocrystals showed a higher rate of dissolution, as seen by an increasein the extent of dissolution. Conclusion: The lumefantrine cocrystal with modified properties was prepared withadipic acid having greater solubility and dissolution rate of the drug.